The ethical implications of resonance theory - Charles Taylor (The Journal of Chinese Sociology, 2023)
Abstract In the first part of this paper, I want to look at the ethical implications of Hartmut Rosa’s Resonance theory for a critical theory of society. I know that this widening of the scope of critical theory is an important objective which Hartmut has pursued. Then I will look at some of the sources of resonance theory in the poetry of the Romantic period. These still provide the basis for important Resonanzachsen today. At the end of this essay, I deal with the issue of the epistemic status of the convictions this poetry inspires.